A new Pardosa species from northern Iran (Araneae, Lycosidae) - Shafaie, Sepideh; Mirshamsi, Omid; Aliabadian, Mansour; Moradmand, Majid; Marusik, Yuri M. (Zootaxa, 2018)
A study of Pardosa pontica (Thorell, 1875) in Iran indicates two distinct morphospecies. A detailed comparison of these morphospecies and types of P. pontica reveals that populations from Mazandaran, Golestan and North Khorasan Provinces of Iran and Balkan Welaýaty of Turkmenistan belong to a newly described species, P. mirzakhaniae sp. n., and populations in western and easternmost Iran belong to P. pontica. Although the two morphospecies differ in colour, size and spination, no molecular differences in 16S rRNA and COI were detected.